A case of conjoined twin's cephalothoracopagus janiceps disymmetros - Hovořáková, Mária; Peterková, Renata; Likovský, Zbyněk; Peterka, Miroslav (Reproductive toxicology (Elmsford, N.Y. 1987), 2008)
Conjoined twins are rare variants of monozygotic twins, which result from an incomplete late division of the embryonic disk. Here we report the rarest case of conjoined twins - the male cephalothoracopagus janiceps disymmetros - born in prenatal week 30, from the archive of the Department of Teratology of the Institute of Experimental Medicine AS CR in Prague. The crown-rump length of each twin, 21cm, corresponded to prenatal week 22 in a normal gravidity. The head, chest and upper portion of the abdomen of the twins were fused. The anatomical features of these extremely rare conjoined twins and the observed external anomalies as a narrow nose with a single nostril, male hypoplastic genitalia, partially duplicated sella turcica, spina bifida and further abnormalities are described and documented.
Keywords: financování organizované; Female; novorozenec; ženské pohlaví; lidé; Infant, Newborn; těhotenství; mnohočetné abnormality; monstra duplicia; hrudník; Financing, Organized; hlava; Male; Thorax; Abnormalities, Multiple; Twins, Conjoined; mužské pohlaví; Pregnancy; Head; Humans